EKSTRATIF BEBERAPA JENIS DAUN BAMBU - Matoke, Manuel; Hutabarat, Lasti; Samosir, Agustinus; Sinaga, Rey (MARSEGU : Jurnal Sains dan Teknologi, 2024)
This research aims to determine the extractive content based on the type of solvent in several types of bamboo leaves. Air dried bamboo leaves were chopped into particles and ground using a blender. After it was finely ground, the sago waste was sieved using 40 and 60 mesh sieves, to obtain bamboo leaf powder with a size of -40/+mesh (TAPPI T 257 cm-85) for testing chemical components. Testing for bamboo leaf powder includes testing the content of cold-water soluble extractive substances, the content of hot-water soluble extractive substances, and the levels of ethanol-toluene soluble extractives. The results of the research showed that the type of bamboo leaf had a significant effect on the levels of cold-water soluble extractive substances, the levels of hot-water soluble extractives, and the levels of ethanol-toluene soluble extractives. Cold water soluble extractive content was 8.4149-10.6612%, hot water soluble extractive 9.1871-10.7843% and ethanol-toluene soluble extractive 4.2009-7.1242%. The solubility of extractives in hot water tends to be higher for all types of leaves and suanggi bamboo tends to contain higher extractives for each type of solvent.